Law Enforcement Role in the Management of Sustainable Natural Resources - Widjaja, Gunawan (Journal of Ecohumanism, 2024)
This study aims to analyze the role of law enforcement in sustainable natural resource management. By examining the linkages between regulations, legal compliance, and their impact on the environment, this study strives to identify factors that influence the effectiveness of law enforcement and provide urgent recommendations to improve natural resource management practices. The study discusses the challenges, including limited resources and institutional capacity, legal complexity and inconsistency, the importance of support from local communities, and international cooperation in law enforcement. This research, conducted using the literature study method, gathers data and information from various academic sources such as journal articles, books, research reports, and relevant policy documents. The results of the literature research show that law enforcement plays a key role in ensuring the sustainability of natural resource management but is faced with various challenges, such as capacity limitations, corruption, and legal complexity. Community participation proves important in streamlining law enforcement, as policies involving local stakeholders are more likely to be accepted and followed. Better international cooperation and regulatory harmonization are urgently needed to address weaknesses in transnational law enforcement. There is a pressing need to implement a more integrated approach to law enforcement, which includes public education, institutional capacity building, and increased transparency and accountability in law implementation.